Sequential structural degradation of red perovskite quantum dots and its prevention by introducing iodide at a stable gradient concentration into the core–shell red perovskite quantum dots. Issue 9 (14th January 2022) - Lee, Hanleem; Trinh, Cuc Kim; So, Mo Geun; Lee, Chang-Lyoul
Abstract : In this study, we studied the degradation mechanism of red perovskite QDs under electric fields to develop a novel strategy for overcoming the low operational stabilities of PeLEDs. Abstract : Perovskite quantum dots (QDs) have been extensively studied as emissive materials for next-generation optoelectronics due to their outstanding optical properties; however, their structural instabilities, specifically those of red perovskite QDs, are critical obstacles in realizing operationally reliable perovskite QD-based optoelectronic devices. Accordingly, herein, we investigated the sequential degradation mechanism of red perovskite QDs upon their exposure to an electric field. Via electrical and chemical characterization, we demonstrated that degradation occurred in the following order: anion-defect-assisted halide migration, cation-defect-assisted migration of I − /Cs + ions, defective gradient I ion distribution, structural distortion, and ion transport/I2 vaporization with defect proliferation. Among these steps, the defective gradient I ion distribution is the key process in the structural degradation of perovskite QDs. Based on our findings, we designed perovskite/SiO2 core–shell QDs with stable gradient I concentrations. Most notably, the operational stabilities of perovskite QD-light-emitting diodes (PeLEDs) fabricated using the perovskite/SiO2 core–shell QDs were approximately 5000 times those of the PeLEDs constructed using pristine perovskite QDs.